Design and development of entertainment robots - Chow, Chee Keong. (2010)
The ability to change behavior and react accordingly is one of the important characteristics of intelligent activity. This intelligent activity is either pre-programmed by the users or are controlled by remote control. This will reduce the involvement of human beings and reduce the danger level. Having a robot that does all the same tasks as human beings would be impossible and difficult to achieve. The Robonova-1 robot is a low-cost humanoid robot that is produced by Hitec. Its limb and joint of both legs and arms are designed similar to human body. It has the ability to walk, flip and dance move easily.